1993
DOI: 10.3109/03008209309041327
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Hyaluronan Binding Proteins Using a Biotinylated Hyaluronan Probe

Abstract: A method for detecting hyaluronan (HA)-binding proteins in transblot assays using biotinylated HA (BHA) is described. Some of the binding characteristics of a novel HA receptor termed RHAMM (Receptor for HA-Mediated Motility) are characterized using this assay. The method is also used to detect other HA-binding proteins in tissue homogenates. This method is semiquantitative, rapid, reproducible, sensitive and therefore of potential use in identifying the levels of HA-binding proteins in different cells and tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 23 publications
1
24
0
Order By: Relevance
“…The blot was incubated with either anti-peptide 168-288 Ab or anti-FP Ab overnight at 4°C and then further probed with biotinylated HA as described previously (29). Streptavidin conjugated with horse radish peroxidase was used to identify bound biotinylated HA.…”
Section: Methodsmentioning
confidence: 99%
“…The blot was incubated with either anti-peptide 168-288 Ab or anti-FP Ab overnight at 4°C and then further probed with biotinylated HA as described previously (29). Streptavidin conjugated with horse radish peroxidase was used to identify bound biotinylated HA.…”
Section: Methodsmentioning
confidence: 99%
“…Analysis of primary astrocytes at various times after sparse plating indicated a progressive decrease in RHAMM expression as cultures became confluent (data not shown). In immunoblots stripped of antibody and reprobed with biotinylated-HA for detection of proteins having HA binding capacity (Hoare et al, 1993), primary astrocytes were found to produce three major HA binding proteins one of which corresponded to the 72 kDa protein recognized by anti-RHAMM antibody. The identity of the other two HA binding proteins that had molecular weights of 140 and 50 kDa and did not react with RHAMM antibody are unknown.…”
Section: Expression Of Rhamm In Glial Cellsmentioning
confidence: 99%
“…HA binding of electrophoresed proteins was analyzed according to previously published protocols using biotinylated HA as a probe. The specificity of this technique has previously been established by showing that digestion of biotinylated HA with streptomyces hyaluronidase abolishes binding and that binding is inhibited by excess unlabelled HA (Hoare et al, 1993). For this assay, immunoblots that had been probed with anti-RHAMM antibody were stripped as previously described (Hall et al, 1993(Hall et al, , 1994 and membranes were then incubated with biotinylated HA (0.001 pg/ml) for 1 h, washed, and developed for chemiluminescence using luminol as described (Amersham, UK).…”
Section: Western Blot and Hyaluronan Binding Analysesmentioning
confidence: 99%
“…Furthermore, most malignant solid tumors and their surrounding stromal tissue contain elevated levels of HA (9). CD44 is the principal cell surface receptor for HA, and it presents at low levels on epithelial, hemopoietic and some neuronal cells (11)(12)(13), and at elevated levels in various carcinoma, lymphoma, breast, colorectal, and lung tumor cells (14)(15)(16)(17). Overexpression of the HA receptors CD44 and RHAMM on cancer cells results in enhanced binding and endocytosis uptake of such compound.…”
Section: Introductionmentioning
confidence: 99%